2017
DOI: 10.1101/209932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular insights into the pathways underlying naked mole-rat eusociality

Abstract: 26Background: 27

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 121 publications
4
11
1
Order By: Relevance
“…Another possibility would be differences in social status. Naked mole-rat queens (dominant reproductive females) have significantly higher tyrosine hydroxylase (Th) and vesicular monoamine transporter (Slc18a2) gene expression in the hypothalamus than subordinate non-breeding animals of either sex [50]. These results parallel our findings in the hypothalamus of females, which may be an indication that females with small social network sizes are dominant to females with large ones, even outside of the reproductive season.…”
Section: Discussionsupporting
confidence: 84%
“…Another possibility would be differences in social status. Naked mole-rat queens (dominant reproductive females) have significantly higher tyrosine hydroxylase (Th) and vesicular monoamine transporter (Slc18a2) gene expression in the hypothalamus than subordinate non-breeding animals of either sex [50]. These results parallel our findings in the hypothalamus of females, which may be an indication that females with small social network sizes are dominant to females with large ones, even outside of the reproductive season.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, these studies have found evidence that the chronic stress of low social status leads to an increase in the expression of proinflammatory genes both in circulating immune cells [16,38] as well as in brain regions important for memory and cognition [40,41]. In one extreme example of social subordination, the reproductive suppression of subordinate, “non-breeder” naked mole rats is apparent at the level of gene expression in reproductive organs [42]. Subordinate female naked mole rats also exhibit different gene expression profiles in the brain — particularly at genes involved in dopamine metabolism, which is implicated in a range of functions from sexual arousal to aggression to cognition [42].…”
Section: Environmental Effects On Genome-wide Gene Regulationmentioning
confidence: 99%
“…In one extreme example of social subordination, the reproductive suppression of subordinate, “non-breeder” naked mole rats is apparent at the level of gene expression in reproductive organs [42]. Subordinate female naked mole rats also exhibit different gene expression profiles in the brain — particularly at genes involved in dopamine metabolism, which is implicated in a range of functions from sexual arousal to aggression to cognition [42].…”
Section: Environmental Effects On Genome-wide Gene Regulationmentioning
confidence: 99%
“…In some species, new breeders undergo a period of accelerated growth, which may be important either for maintaining dominance or for supporting high fecundity [7][8][9][10][11][12] . While substantial gene regulatory divergence with breeding status has been described for the brain and some peripheral organs [13][14][15] , we know little about the gene regulatory shifts responsible for breeder-associated growth patterns. These processes are key to understanding both the basis for, and limits of, status-driven differences in growth and development.…”
mentioning
confidence: 99%